VALUE ORIENTATIONS OF THE PERSONALITY AND THE PROBLEMS OF THE MODERNIZATION OF CONTEM PORARY UKRAINIAN EDUCATION - Ovsyankina, L. (Continuing Professional Education: Theory and Practice, 2019)
Today, Ukrainian society is in a state of crisis that exacerbates conflicting trends in the minds of people and their behavior, the imbalance values of society and the individual. Vector address this complex social problem may be modernization of contemporary Ukrainian education, aimed at qualitative changes in its methodology and content and strengthening the practical component. Modernization should be based on fundamentalization, humanization and continuity. Also it should be directed aims to search for certain pedagogical innovations, aimed at the achievement of such an important result, as the Personality of the XXI century. Fundamentalization of education includes two components: fundamentalization of the educational process and fundamental educational knowledge. The essence of humanizing of the education space consists of the specific orientation, style of thinking and human activities. Continuity of education is achieved by the harmonizing of the three principles: the educational needs of the individual, educational capacity of the institutional forms to satisfy these wants and opportunities of the social system to ensure the conditions for the transformation of the educational need for the sustainable development